NETosis may play a role in the pathogenesis of Hashimoto’s thyroiditis - Xiao, Fang (Int J Clin Exp Pathol, 2018)
Neutrophil extracellular traps (NETs) are shown to play important roles in the progression or development of systemic autoimmune diseases. However, implication of NETs or NETosis in the pathogenesis of non-systemic autoimmune diseases such as Hashimoto’s thyroiditis (HT), a chronic inflammatory organ-specific autoimmune disease, has not been previously reported. In the present study, our results demonstrate that the concentration of NET products, neutrophil elastase (NE) and proteinase 3 (PR3) in plasma, are significantly higher in the patients with HT than in healthy controls, respectively. In addition, PR3 concentration in plasma was positively associated with the titers of autoantibodies against thyroglobulin (TGAb) and thyroid peroxidase (TPOAb) in serum, respectively. Consistently, NETosis was more markedly induced in neutrophils derived from the HT patients than controls. Concomitantly, IL-6 production in the NETosis induction system in the neutrophils from the patients was significantly higher than those in controls. Moreover, serum from HT patients but not healthy controls induced more pronounced NETosis in neutrophils. Meanwhile, our immuno-fluorescence staining results showed that NETs from the HT patients contained autoantigens. These findings together indicate roles for NETs and/or NETosis in autoantibody generation as well as pathogenesis of HT. Therefore, the underlying mechanisms of NETs in the pathogenesis of HT warrant further study.